A Quantitative Serum Proteomic Analysis Helps to Explore the Comprehensive Mechanism and Identify Serum Biomarkers of Shengmai Injection’s Effect on Isoproterenol-Induced Myocardial Ischemia in Rats - Zhang, Xiaoping; Zhang, Jie; Ji, Xiangyu; Wei, Zhenzhen; Ding, Baoyue; Liu, Guoqiang; Lv, Xiaoqing; Zheng, Yongxia; Zhan, Shuyu (Frontiers in Pharmacology, 2021)
Shengmai injection (SMI), a traditional Chinese medicine formula with the nature of multi-component and multi-target, has been widely used in clinic for treating cardiovascular diseases in China; However, its comprehensive mechanism of action remains unclear. In this study, a TMT-based quantitative serum proteomics was performed to explore SMI’s global mechanism and helps to identify serum biomarkers of its effect on isoproterenol (ISO)-induced myocardial ischemia rats. The results of TMT-based proteomic analysis identified 227, 100 and 228 differently expressed proteins (DEPs) for the Model comparing to the Control group, SMI pretreatment + Model comparing to the Model group and SMI pretreatment + Model comparing to the Control group, respectively. Based on bioinformatics analyses of gene ontology (GO), KEGG pathways and the protein–protein interaction (PPI) networks for the DEPs, it is concluded that the comprehensive mechanism of SMI’s effect on ISO-induced myocardial ischemia injury which at least include regulation of energy metabolism, reducing endothelial cell permeability, regulation of vessel and cardiac contractility, anti-inflammation and prevention of cell apoptosis. Furthermore, 10 common DEPs were found and 6 of them were regulated in Model vs. Control group while back-regulated in SMI pretreatment + Model vs. Model group. Among them, three functional proteins of glyceraldehyde-3-phosphate dehydrogenase (GAPDH), Fas apoptotic inhibitory molecule 3 (FAIM3) and uncharacterized protein (M0R5J4) which were verified by the PRM analysis might be the potential serum biomarkers on SMI’s effects. Overall, this serum proteomics of SMI not only provides insights into the comprehensive mechanism underlying SMI’s effects on ischemic heart disease but also helps to identify serum biomarkers for directing SMI’s cardioprotective effects.